A Journey in the Land where Art, Design, and Research Intersect - Loi, Daria (Art/Research International)

(untitled) (University of Alberta, 2025)
Through a series of projects, this article discusses the role that objects play when art, design, and research intersect. The article is divided into nine sections. After a preamble, I discuss The Pea Project, key to understanding how anomalous objects and odd experiences stimulate reflectiveness, curiosity, creativity, and collaboration. “A Surrealist Encounter” discusses how contexts can be designed to foster reflective and collaborative practice, while Reflective Probes focuses on artifacts designed to stimulate reflective practice. I then discuss activation of receptive modes of engagement through playful triggers and travelling containers. Progetto in Memoriam further explores art, research, and ethnographic practices, and Debris explores simultaneous roles as a designer, artist and ethnographer. While section 8, They Said, looks at how prior learnings were used to deepen my understanding of self, the final section provides conclusive remarks, reiterating the opportunities that exist when art, design, and research intermingle and collide.